Acute radiation exposure in mice reveals traces of oxidation-mediated modifications in serum albumin - Masaru Yamaguchi; Yota Tatara; Yoshiaki Sato; Ikuo Kashiwakura (PLoS ONE, 2025)
High doses of ionizing radiation induce specific oxidation-mediated modifications on the sequence of amino acid that constitutes serum albumin, but the time-dependent response thereafter is unclear. We, therefore, used liquid chromatography coupled with tandem mass spectrometry to profile oxidation-mediated modifications in serum collected from mice subjected to total body X-ray irradiation (TBI) at 20-day intervals up to day 80. In TBI mice, albumin structural regions were generally glycated and oxidatively modified, and in particular, oxidative modifications of serum albumin (OMSA) were observed on either analysis day in eight sequences containing the following amino acid residues: OMSA9 (oxidation of lysine residue (Lys)-97), OMSA12 (oxidation of methionine residue (Met)-147), OMSA21 (oxidation of tyrosine residue (Tyr)-287), OMSA22 (oxidation of proline residue (Pro)-306), OMSA25 (oxidation of Lys-310), OMSA29 (oxidation of Pro-390), OMSA40 (oxidation of Tyr-476), and OMSA39 (nitration of Tyr-476). Interestingly, some significant OMSA sequences induced by TBI were maintained even after 41 times the half-life of albumin. These results suggest that exposure to ionizing radiation induces specific oxidative modifications in serum albumin, and there are specific amino acid residues that are sensitive to these modifications. Furthermore, these could be applied as novel biomarkers to estimate the presence or history of radiation exposure.